Families and mobile devices in museums: designing for integrated experiences - Rennick-Egglestone, Stefan; Brundell, Patrick; Koleva, Boriana; Roussou, Maria; Chaffardon, Christophe; Benford, Steve (ACM, 2016)
This paper presents an observational study of eight families engaging with a bespoke tablet experience produced for a space science centre. It documents the various ways in which family members orientate themselves to the usage of technology in this environment, with a particular focus on the work done to manage the tablet and facilitate the engagement of younger children with the narrative of the experience. These findings are considered in the broader context of the need to design experiences that cater for engagement by families as a whole. We conclude by motivating the need for technologies that are robust in light of regular disengagement and by family members, and which provide functionality to directly support facilitation work.